2015
DOI: 10.1159/000430382
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells for Predicting the Prognostic of Patients with Hepatocellular Carcinoma: A Meta Analysis

Abstract: Background/Aims: The prognostic value of circulating tumor cells (CTC) detected in hepatocellular carcinoma (HCC) patients is currently under debate. We conducted a meta-analysis of available studies to assess its prognostic value for patients diagnosed with HCC. Methods: Medline, Ovid Database, Embase, The Science Citation Index, and Cochrane library, search was conducted on all studies reporting the outcomes of interest. The studies were set up according to the inclusion/exclusion criteria. Using a random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 52 publications
(53 reference statements)
2
57
1
Order By: Relevance
“…The numbers of CTCs were closely correlated with portal vein thrombosis, tumor infiltration, prognosis and Child-Pugh grade [61,64,69] . Most of the studies have shown that before liver resection or transplantation, tumor cells from the primary lesions were detached and threw into the blood being the early event of HCC metastases.…”
Section: Ctcsmentioning
confidence: 92%
See 1 more Smart Citation
“…The numbers of CTCs were closely correlated with portal vein thrombosis, tumor infiltration, prognosis and Child-Pugh grade [61,64,69] . Most of the studies have shown that before liver resection or transplantation, tumor cells from the primary lesions were detached and threw into the blood being the early event of HCC metastases.…”
Section: Ctcsmentioning
confidence: 92%
“…Most of the studies have shown that before liver resection or transplantation, tumor cells from the primary lesions were detached and threw into the blood being the early event of HCC metastases. Fan et al [69,70] reported that the tumor recurrence after resection was associated with the number of CTCs detected, maybe because CTCs were still surviving into the blood [70][71][72] . However, the role of CTCs and HCC recurrence require further investigations.…”
Section: Ctcsmentioning
confidence: 99%
“…CTCs have been reported in patients with HCC, but the characteristically low EpCAM cell surface expression in this tumor type has limited the utility of standard CTC measurements (12,13). To establish a high-throughput, bloodbased assay for HCC that would have broad applicability, we therefore adapted the microfluidic CTC-iChip isolation platform with a digital RNA-PCR readout combining liver-specific transcripts whose expression is retained in HCC.…”
Section: Significancementioning
confidence: 99%
“…These cells have recently been exploited for guiding clinical management, evaluating curative efficacy, predicting prognosis and monitoring tumor recurrence [7]. The CellSearch system is the only CTC detection technology approved by the FDA.…”
Section: Introductionmentioning
confidence: 99%